“My wife made me”: motivations for body and beauty work among older Korean and Chinese migrant adults in Australia - Shu, Zhu; Elfving-Hwang, Joanna (Taylor & Francis, 2024)
This article examines how older Korean and Chinese migrants living in Perth, Australia, engage in various beauty, grooming and fitness practices to negotiate “successful ageing” in transnational contexts. Drawing on semi-structured interviews with 30 men and women aged between 60 and 89, we examine what social meanings are attached to these practices, and how the transnational context of living in Australia has influenced the participants’ perceptions of ageing and presentation of self in later life. Migration in later life is often considered in relation to the ‘host’ countries values and social practices, which can make it difficult for individuals to settle and feel a sense of belonging especially in later life. In this article, we will illustrate how gender, class, and cultural dispositions intersect and link with possibilities for defining and redefining successful ageing in migrant contexts. This study illustrates how successful ageing emerges as a malleable concept that draws on ideas of an ideal ageing body from the cultural values of the ‘home’ country, rather than the ‘host’ country. The findings illustrate how in everyday lived experience, the transnational habitus does not always necessarily result in a ‘divided habitus’ where the values of the ‘home’ country and that of the ‘host’ country are in conflict – even when the migration experience is relatively recent. Quite the contrary, the way the participants utilise everyday beauty, fitness and grooming practices to maintain a future-focused self in the context of ‘home’ country’s age-appropriate body ideals to perform signifiers of ‘successful migrant living’ point to the positive aspects that appearance management can have on an individual in later life, particularly in migrant contexts.